Efficiency of granulated baits with sulfluramid or clorpirifos against Acromyrmex octospinosus (Hymenoptera: Formicidae) in a region of the humid tropic - CRUZ, ADALTON P. DA; ZANUNCIO, JOSE C.; ZANETTI, RONALD; PEREIRA, JOSE M. M. (Revista Colombiana de Entomología, 2000)
The efficiency of granulated baits with sultluramid (0.3%) or chlorpirifos (0.45%) was evaluated againstAcromyrmex octospinosus (Hymenoptera: Formicidae) in an area reforested with a Eucalyptus grandis x Eucalyptus urophylla hibrid of Jari Celulose S.A. in Almerim, State of Pará, in the Amazonian Region of Brazil from November 1994 to March 1995. The results of these baits were compared with those of another one with dodecachlor (0.45%) applied at a rate of 10 grams per square meter of ant nest. The bait with sultluramid at 6, 8 and 10 grams per square meter of ant nest showed 77.78, 100 and 100% control of A. octospinosus while the chlorpirifos bait showed 33.33, 22.22 and 55.56% control of this ant in 5, 10 and 20 grams per square meter of ant nest respectivelly. The sultluramid bait ata rate of 8 grams per square meter of ant nest is recomended for A. octospinosus control in the Almerim Region, State of Para, Brazil.